2021
DOI: 10.1109/access.2021.3052884
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Neural Synchronization Using Nature Inspired Whale Optimization

Abstract: In this article, a whale optimization-based neural synchronization has been proposed for the development of the key exchange protocol. At the time of exchange of sensitive information, intruders can effortlessly perform sniffing, spoofing, phishing, or Man-In-The-Middle (MITM) attack to tamper the vital information. Information needs to be secretly transmitted with high level of encryption by preserving the authentication, confidentiality, and integrity factors. Such stated requirements urge the researchers to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…In each iteration, the ight speed is limited within the interval [-Vmax, Vmax]. Each element in the particle swarm starts from the initial position and velocity and carries out iterative calculation according to Equations ( 1) and ( 2) until the termination condition of the algorithm is met [32]. Many scholars have improved the PSO algorithm.…”
Section: Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…In each iteration, the ight speed is limited within the interval [-Vmax, Vmax]. Each element in the particle swarm starts from the initial position and velocity and carries out iterative calculation according to Equations ( 1) and ( 2) until the termination condition of the algorithm is met [32]. Many scholars have improved the PSO algorithm.…”
Section: Particle Swarm Optimization Algorithmmentioning
confidence: 99%
“…The measurement of the distance between weights using the rule of Euclidean is not even technically applicable. Sarkar and Mandal [34], Sarkar [33], Sarkar and Mandal [35], Mandal and Sarkar [19], Sarkar et al [36] proposed schemes that enhanced the security of the protocol by enhancing the synaptic depths of TPM and henceforth counteracting the attacks of the brute power of the attacker. It is found that the amount of security provided by the TPM synchronization also can be improved by introducing a large set of neurons and entries of each neuron in the hidden layers.…”
Section: Related Workmentioning
confidence: 99%
“…This approach took a long time to complete the synchronization process. Sarkar et al [14], [15], [16], [17], [18] suggested a framework that increased protocol security by improving the Tree Parity Machine's weight range (TPM). It was discovered that increasing the number of neurons in the secret layers increases the level of TPM synchronization security.…”
Section: Related Workmentioning
confidence: 99%